Extended treatment of venous thromboembolism: a systematic review and network meta-analysis. Issue 7 (16th October 2018) - Wang, Kang-Ling; van Es, Nick; Cameron, Chris; Castellucci, Lana A; Büller, Harry R; Carrier, Marc
Abstract : Objective: To evaluate efficacy and safety of oral anticoagulant regimens and aspirin for extended venous thromboembolism (VTE) treatment. Methods: We searched MEDLINE, Embase, CENTRAL and conference proceedings for randomised controlled trials studying vitamin K antagonists (VKAs), direct oral anticoagulants (DOACs) or aspirin for secondary prevention of VTE beyond 3 months. ORs (95% credible intervals) between treatments were estimated using random-effects Bayesian network meta-analysis. Results: Sixteen studies, totaling more than 22 000 patients, were included. Compared with placebo or observation and with aspirin, respectively, the risk of recurrent VTE was lower with standard-intensity VKAs (0.15 (0.08 to 0.24) and 0.23 (0.09 to 0.54)), low-dose factor Xa inhibitors (0.16 (0.06 to 0.38) and 0.25 (0.09 to 0.66)), standard-dose factor Xa inhibitors (0.17 (0.08 to 0.33) and 0.27 (0.11 to 0.65)) and the direct thrombin inhibitor (0.15 (0.04 to 0.37) and 0.23 (0.06 to 0.74)) although the risk of major bleeding was higher with standard-intensity VKAs (4.42 (1.99 to 12.24) and 4.14 (1.17 to 18.86)). Effect estimates were consistent in male patients and those with index pulmonary embolism or with unprovoked VTE and in sensitivity analyses. In addition, compared with placebo or observation, the risk of all-cause mortality was reduced with standard-intensity VKAs (0.44 (0.20 to 0.87)) and low-dose factor Xa inhibitors (0.38 (0.12 to 0.995)). Conclusions: Standard-intensity VKAs and DOACs are more efficacious than aspirin for extended VTE treatment. Despite a higher risk of major bleeding, standard-intensity VKAs was associated with a lower risk of all-cause mortality. Since overall efficacy and safety of standard-intensity VKAs and DOACs are in equipoise, patient factors, costs and patient preferences should be considered when recommending extending anticoagulation treatment.